Acute ST‐elevation Myocardial Infarction in Young Patients: 15 Years of Experience in a Single Center - Chua, Su‐Kiat (Clin Cardiol, 2010)
BACKGROUND: There have been few studies done regarding young patients with ST‐elevation myocardial infarction (STEMI). The purpose of this study was to investigate the clinical characteristics and coronary angiographic features in young patients with STEMI. METHODS: We collected data on 849 consecutive patients with STEMI from 1992 to 2006. Baseline clinical characteristics, coronary anatomy, and outcome were compared in young (≤45 yrs) and older patients (>45 yrs). RESULTS: Young patients presented 11.6% of all patients with STEMI. These patients were predominantly male (92.9% vs 80.3%, P < 0.001), more likely to smoke (75.8% vs 47.2%, P < 0.001), obese (48.2% vs 27.9%, P = 0.002), have higher triglyceride levels (176.9 ± 153.8 mg/dL vs 140.7 ± 112.7 mg/dL, P = 0.005), and lower high‐density lipoprotein cholesterol (37.1 ± 7.9 mg/dL vs 42.8 ± 14.3 mg/dL, P = 0.005) than older patients. Also, younger patients had a shorter hospital stay (7.1 ± 4.9 d vs 8.5 ± 6.7 d, P = 0.04), less in‐hospital morbidity (29.3% vs 39.7%, P = 0.02), and mortality (3.0% vs 12.3%, P = 0.002). Killip class III or IV could predict in‐hospital morbidity and mortality in young patients. Both groups had similar rates of repeated percutaneous coronary intervention (PCI; 45.5% vs 41.5%, P = 0.23) and reinfarction (6.1% vs 3.2%, P = 0.32). Mortality rate during follow‐up was significantly lower in younger patients (3.0% vs 19.6%, P < 0.001). CONCLUSION: Cigarette smoking, obesity, and dyslipidemia were the most important modifiable risk factors in young patients with STEMI. These patients had a better outcome than older patients without differences in repeated PCI and reinfarction between them. Only Killip class III or IV could predict in‐hospital morbidity and mortality in young patients with STEMI. Copyright © 2010 Wiley Periodicals, Inc.